Application of melanin pigment from actinobacteria in textile industry (Nepal Journal of Environmental Science, 2025)
Actinobacteria are known to produce pigments which has many industrial applications. Melanin is one of the pigments produced by many of the actinobacteria. In this paper, the application of melanin in textile industry is studied. The actinobacteria were isolated from the soil samples. The three isolates were shown to produce melanin which was identified to belong to the genus Streptomyces and Nocardia. Melanin pigment was extracted from actinobacteria using starch casein, tyrosine and oatmeal media. The production of the melanin pigment was checked on both solid agar and liquid media. The application of melanin pigment was checked in colouring the white cotton fabric. When used for colouring the fabric, the extracted pigment gave successful outcomes. This study has paved the way for important application of melanin pigment in textile industries.